RESEARCH ON THE IMPACT OF CUSTOMER PRESSURE AND GREEN PERCEPTION ON GREEN INNOVATION: AN EMPIRICAL STUDY IN VIETNAM - Anh, Nguyen Thi Mai; Thuy, Tran Thu; Thao, Tran Phuong; Hien, Nguyen Thi Dieu (Veredas do Direito, 2026)
This study aims to evaluate the impact of customer pressure and green perception on green innovation within logistics enterprises in Vietnam, through the mediating role of knowledge sharing. Data were collected from logistics companies operating in Vietnam using a questionnaire - based survey method. The research model was tested using Structural Equation Modeling. The results indicate that both customer pressure and green perception have a positive impact on knowledge sharing within the organization. Furthermore, knowledge sharing significantly influences green innovation. These findings imply that the combination of external market pressures and internal strategic perceptions can drive enterprises to implement green innovation through the internal mechanism of knowledge sharing. Based on these results, the study proposes managerial implications to help logistics firms enhance their green innovation capabilities towards sustainable development.